Application of an adaptive tuned vibration absorber on a dual lay-shaft dual clutch transmission powertrain for vibration reduction. (15th April 2019) - Gao, Pu; Walker, Paul D.; Liu, Hui; Zhou, Shilei; Xiang, Changle
Highlights: Analyzing effects of engine speed, gear ratio and gear shifting process on dominant frequency. Study on relationships of system natural frequency, dominant frequency and ATVA natural frequency. Proposal of installation position, stiffness range and ATVA frequency tuning scheme. Abstract: This paper investigates the application of adaptive tuned vibration absorbers (ATVAs) to lightly damped automotive powertrains. To achieve this, a vibration characteristic analysis of a dual lay-shaft dual clutch transmission (DCT)-equipped powertrain system was performed, including a natural frequency evaluation and sensitivity studies. Transient responses due to gear changes and variations of both the gear ratio and engine speed were also evaluated. The results demonstrate that the impact of ATVAs on transient responses during gear changes is minimal, suggesting that these short-duration transients are outside the scope of application for ATVAs. However, as excitation forces originate from the engine, speed has a significant impact on excitation frequency. Furthermore, the gear ratios significantly influence the engine operating range and natural frequency in any particular gear. Therefore, variations of engine speeds and gear ratios are the main influencing factors affecting the dominant excitation frequency. Consequently, the relationships among the system natural frequencies, the dominant external excitation frequency and the inherent frequency of the ATVA are comprehensively studied. By investigating the relationships among the dominant external excitation frequency and system natural frequencies and the system sensitivity analysis results, the installation position, stiffness range and optimal frequency tuning scheme of the ATVA can be determined. The results were applied to a DCT powertrain with continuously changing engine speeds and an ATVA with corresponding variable stiffness, and a frequency tuning scheme is installed on the powertrain. By comparing the simulation results, the effectiveness and reliability of the presented method can be verified.